Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT Supraco Indonesia Jakarta - Benita Apta Nadia; Taat Kuspriyanto; Yunidyawati Azlina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Employee performance is one of the most important factors that determine the achievement of company goals. In the modern world of work, workload and work environment are two factors that are most often considered in influencing employee performance. As a company engaged in the service sector. As a company engaged in the field of supporting services for the oil and gas industry, PT Supraco Indonesia requires high-performing employees to provide the best service to its clients. This study aims to determine how much influence motivation and service levels have on customer satisfaction in participating in computer training. The research method used is a quantitative approach with data collection techniques using random sampling or purposive sampling, where the entire population of 56 respondents was used as a sample. The data collection instrument used a questionnaire with a Likert scale. Data analysis was carried out using SPSS 27 software with multiple linear regression techniques. The results of the study show that the company size variable in particular, Workload (X1) has a significant effect on Employee Performance with a significant t-value on the level of work environment (X2) also has a significant effect with a significant t-value simultaneously, both have a significant effect on employee performance with a calculated F-value. Meanwhile, the coefficient of determination value shows that the influence of workload and work environment on employee performance is significant.